Effect of Exercise on Metabolic Syndrome Variables in Breast Cancer Survivors - Gwendolyn A. Thomas; Marty Alvarez-Reeves; Lingeng Lu; Herbert Yu; Melinda L. Irwin (International Journal of Endocrinology)
Objective. Breast cancer survivors are highly sedentary, overweight, or obese, which puts them at increased risk for comorbid chronic disease. We examined the prevalence of, and changes in, metabolic syndrome following 6 months of an aerobic exercise versus usual care intervention in a sample of sedentary postmenopausal breast cancer survivors. Design and Methods. 65 participants were randomized to an aerobic exercise intervention (EX) (n=35) mean BMI 30.8 (±5.9) kg/m2 or usual care (UC) (n=30) mean BMI 29.4 (±7.4) kg/m2. Metabolic syndrome prevalence was determined, as well as change in criteria and overall metabolic syndrome. Results. At baseline, 55.4% of total women met the criteria for metabolic syndrome. There was no statistically significant change in metabolic syndrome when comparing EX and UC. However, adhering to the exercise intervention (at least 120 mins/week of exercise) resulted in a significant (P=.009) decrease in metabolic syndrome z-score from baseline to 6 months (-0.76±0.36) when compared to those who did not adhere (0.80±0.42). Conclusions. Due to a higher prevalence of metabolic syndrome in breast cancer survivors, lifestyle interventions are needed to prevent chronic diseases associated with obesity. Increasing exercise adherence is a necessary target for further research in obese breast cancer survivors.